Once upon a summer eaudiobook Seasons of the heart (oke) series, book 1. - Oke, Janette (Seasons of the Heart, 2003)
Best-selling author of Too Long a Stranger and Julia's Last Hope, Janette Oke is loved for her inspirational novels. In Once Upon a Summer, Oke weaves the tender tale of 12-year-old, Joshua, who has been raised by his 18-year-old aunt and their grandparents. He has grown accustomed to their close-knit family, but that is all about to change when Joshua's aunt considers marriage. Johnny Heller touchingly narrates the trials of faith this family must face.